Trophic ecology of Scinax rostratus (Peters, 1863) and Scinax ruber (Laurenti, 1768) (Anura: Hylidae) in tropical dry forests of northern Colombia - Blanco Torres, Argelina (2017)
We describe the diet of two syntopic Scinax species, S. rostratus and S. ruber, from northern lowlands of Colombia. These frogs do not seem to exhibit a marked preference for the consumption of a particular type of prey. However, in their diets, orthopterans were a well-represented category. Scinax ruber showed a positive and significant relationship between the size of the jaw and the average volume of consumed prey. The diets of both species overlap (54%), containing orthopterans, hemipterans and acari. Considering the trophic characteristics of both species, we classify them as generalist predators that use the sit-and-wait strategy to capture their prey.